2008
DOI: 10.1088/0967-3334/29/4/002
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of heartbeat interval series in young healthy trained and untrained men

Abstract: The origin of heart rate variability (HRV) is largely in parasympathetic activity. The direct influence of sympathetic activity and other control mechanisms, especially at an increased HR, is not well understood. The objectives of the study were to investigate the influence of increasing HR on the properties of heartbeat interval (RR) series in young healthy subjects. ECG was recorded in 9 trained and 11 untrained young men during supine rest, standing, incremental running exercise and relaxation. During exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 23 publications
(39 reference statements)
6
39
0
1
Order By: Relevance
“…5.a), it has also been found that exercise modifies the distribution of the power spectrum by reducing the low frequency components [16,34,35] and introducing very high frequencies related to the respiration rate [36], decreases the sample entropy [37]. Also, the linear correlations measured by the short scale DFA exponent (α 1 ) are not only reduced with exercise [37,38] but also can be correlated with the intensity of the exercise [39]. Nevertheless it is fair to say that the opposite result can also be also found in the literature [40].…”
Section: Example Of Natural Signals: Heart Rate During Rest and Ementioning
confidence: 99%
“…5.a), it has also been found that exercise modifies the distribution of the power spectrum by reducing the low frequency components [16,34,35] and introducing very high frequencies related to the respiration rate [36], decreases the sample entropy [37]. Also, the linear correlations measured by the short scale DFA exponent (α 1 ) are not only reduced with exercise [37,38] but also can be correlated with the intensity of the exercise [39]. Nevertheless it is fair to say that the opposite result can also be also found in the literature [40].…”
Section: Example Of Natural Signals: Heart Rate During Rest and Ementioning
confidence: 99%
“…This was motivated by the fact that in some practical circumstances short-term recordings of HRV data are more likely to be obtained [3,24,33,36]. Also important to consider is the analysis of any short-term database already collected that could be of interest to characterise using a fractal framework, and the assessment of nonsteady-state conditions such as dynamical exercise [20,39]. To our knowledge the statistical possibility of obtaining reliable estimations of a 1 has not been explicitly addressed or mentioned in studies using short-term recordings of HRV data [3,16,20,36,37,43,45,48].…”
Section: Introductionmentioning
confidence: 99%
“…For example, measures of HR complexity while under vagal blockade have been shown to be unaffected, 31,32 reduced 20 or almost completely abolished. [33][34][35] Further, HR complexity is reduced by standing 36 and increased during low-intensity dynamic exercise 25 but unaltered during sympathetic blockade, 35 passive head-up tilt 25 or autonomic stress. 35 Differences in circulating catecholamine concentrations evoked by each stimulus have been proposed to explain divergent complexity responses, 25 but this concept requires further investigation.…”
Section: Validity Of Cardiac Autonomic Measuresmentioning
confidence: 96%
“…Examination of the short-term fractal scaling exponent (α 1 ) determined by detrended fluctuation analysis has also produced conflicting results. This measure, which quantifies the fractal-like correlation properties of the HR signal, has been shown to be reduced by norepinephrine infusion, 37 cold face immersion 38 or progressive dynamic exercise 36 and increased during standing, 36 low-intensity dynamic exercise, 25 passive head-up tilt 25 or cold hand immersion, 38 and unaffected 35 or increased 25,32 by atropine administration. Nonetheless, similar to linear HRV, the majority of non-linear measures of HR appear to be impacted more by cardiac vagal than sympathetic modulation.…”
Section: Validity Of Cardiac Autonomic Measuresmentioning
confidence: 99%